LOCAL WISDOM OF STRUCTURE AND BUILDING SYSTEM TRADITIONAL ARCHITECTURE IN RESPONDING TO NATURE - Parmonangan Manurung (International Journal on Livable Space, 2017)
ABSTRACTTraditional architecture was built on a tradition inherited from one generation to the next. As a country which has hundreds of tribes, Indonesia has hundreds of traditional architecture designed by the ancestors to fulfill the function as well as responding to natural context. The aim of this research is to find out how the structural and building system traditional architecture in this country respond its natural conditions as the context. The method used is qualitative descriptive with the analysis of some traditional architecture which have been visited and conducted a theory review. The results showed that the traditional architecture in Indonesia had been designed to respond to nature as context. From the discussion, it can be concluded that traditional architecture in each region has an approach in aligning themselves with nature as context.Keywords: Local wisdom, traditional architecture, earthquake, climate, context.